Effect of foliar application treatment with gibberellic acid (GA3) on some biochemical and productive traits in Kasper hybrid (Zea mays L. Var saccharata) under Drought Stress - درويش, مجد (Latakia University Journal -Biological Sciences Series, 2024)
The experiment was carried out during the agricultural season 2023 in Damsarkho village- Lattakia– Syria by the cultivation of sweet corn seeds, Kasper hybrid, in plastic pots (40×60 cm) that were distributed according to the randomized complete design (RCD) with three pots per treatment. The research aimed to study the effect of plant spraying with the gibberellic acid (30, 45 and 60 ppm) on some biochemical and productive characteristics of sweet corn under water stress conditions (15, 30 and 45 %) equivalent to an osmotic pressure (-0.7, -1.4 and -2.1) MPa. So, the biochemical (chlorophyll and carotenoids contents (µg/g FW), proline content (µg/g FW)), and the productivity characteristics (ear length (cm), number of rows per ear (rows/ear) and grain yield (g/ear) have been studied. The water stress, negatively affected on growth, development and productivity of sweet corn. The treatment with gibberellic acid, especially at (30 and 45 ppm), increased the growth and productivity of plant, as indicated in all the studied traits and characteristics. The gibberellic acid treatment, particularly at (30 ppm), under water stress conditions also improved the chemical and productive characteristics, and increased its tolerance to water stress. Thus, it can be proposed to spray the gibberellic acid with (30 ppm) concentrations considering to its observed role in stimulating the growth of sweet corn plants, Kasper hybrid, increasing the grain yield and improving the plants tolerance to water stress.